2021
DOI: 10.3389/fimmu.2021.648917
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Prognostic Implications of the Components and Signatures in the Immune Microenvironment of Pancreatic Ductal Adenocarcinoma

Abstract: Background: The treatment modalities for pancreatic ductal adenocarcinoma (PDAC) are limited and unsatisfactory. Although many novel drugs targeting the tumor microenvironment, such as immune checkpoint inhibitors, have shown promising efficacy for some tumors, few of them significantly prolong the survival of patients with PDAC due to insufficient knowledge on the tumor microenvironment.Methods: A single-cell RNA sequencing (scRNA-seq) dataset and seven PDAC cohorts with complete clinical and bulk sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 58 publications
(65 reference statements)
0
28
0
Order By: Relevance
“…CD161 showed a strong positive relationship with these inhibitory immune checkpoints, which lead to the suppression of immune response to gliomas. Moreover, we chose seven immune system–related metagene clusters as markers for immunological states, 14 , 15 , 16 including hemopoietic cell kinase (HCK), lymphocyte‐specific kinase (LCK), major histocompatibility complex (MHC), signal transducer and activator of transcription 1/2 (STAT1/2), interferon, and IgG. 17 , 18 Corrgrams showed that CD161 and seven metagene clusters were significantly positively correlated in the CGGA and TCGA databases (Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…CD161 showed a strong positive relationship with these inhibitory immune checkpoints, which lead to the suppression of immune response to gliomas. Moreover, we chose seven immune system–related metagene clusters as markers for immunological states, 14 , 15 , 16 including hemopoietic cell kinase (HCK), lymphocyte‐specific kinase (LCK), major histocompatibility complex (MHC), signal transducer and activator of transcription 1/2 (STAT1/2), interferon, and IgG. 17 , 18 Corrgrams showed that CD161 and seven metagene clusters were significantly positively correlated in the CGGA and TCGA databases (Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…In humans, cancer patients often present with reduced numbers of iNKT cells and/or impaired iNKT cell function [35][36][37][38]. In contrast, iNKT cell infiltration into tumors is associated with a good prognosis in chronic lymphocytic leukemia, neuroblastomas, colorectal carcinoma, and pancreatic adenocarcinoma [39][40][41][42][43]. iNKT cell immunosurveillance is likely mediated by inflammatory cytokines or recognition of tumor-associated glycolipids or stress-induced glycolipid antigens presented by CD1d positive tumor cells, or by antigen-presenting cells (APCs) [44][45][46][47].…”
Section: Inkt Cells In Cancermentioning
confidence: 99%
“…Using algorithms such as ssGSEA, the expression level of markers can reflect the infiltration of specific cell types in tumor tissue. Through the complete follow-up data of multiple cohorts, the relevance between the relative infiltration level of specific cell types and the survival rate of patients can be determined [ 11 ]. For instance, based on the epigenetic properties of immunomodulatory cytokine genes, methylation of these genes has been found to be related to overall survival (OS), disease-specific survival, and disease progression in PAAD patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%